British reconnaissance trips in Iraq and the Persian Gulf 1871- 1914 AD. - صلاط أيمن; شحود داليا (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
The research studies the movement of British travelers and their wanderings between Arab tribes without any obstacles. Due to the weakness and collapse of the ruling Ottoman Empire. And the focus of those trips was based on accurate information gathering, getting to know the conditions of the country and revealing its weaknesses, because of the ease of its occupation later, and this is what happened when Britain occupied Iraq in 1914 AD. Every traveler left memoir, maps, and geographic and demographic articles collected with the government of British India, which prevented their publication for use in war planning. And so it turns out that these travelers were spies. They made great efforts to serve their government, which in turn depended on them. And they were able to endure the harsh desert environment on the one hand, and deal with the Bedouins on the other hand. Taking into account the necessity of understanding the Islamic religion and mastering the Arabic language. The role of women also emerged on scouting trips. British woman carried out espionage acts no less important than the brave man. Especially prior to the outbreak of the First World War 1914-1918 AD.